USING WHATSAPP GROUP AS LANGUAGE LEARNING STRATEGY (LLS) TEACHING TOOL TO IMPROVE ACADEMIC WRITING PERFORMANCE OF EFL STUDENTS - Masrul; Santi Erliana (IKIP Siliwangi, 2024)
This study aimed to examine the impact of Whatsapp-based instruction in using indirect Language Learning Strategies (LLS) on their academic writing performance. The participants were Indonesian 60 female and 52 male students aged 16 to 26. The current study was experimental in design, with quasi pre and post-tests for the experimental and control groups. There was one independent (experimental) variable and two dependent variables. The post-test treatment's means were all higher than the pre-test treatment due to the six indications. In other words, from the pre- to post-tests, all indicators increased on average. In accordance with current trends, Whatsapp can be employed as an LLS teaching tool.